Incorporated Fish Oil Fatty Acids Prevent Action Potential Shortening Induced by Circulating Fish Oil Fatty Acids - Den Ruijter, Hester M.; Verkerk, Arie O.; Coronel, Ruben (Frontiers in Physiology, 2010)
Increased consumption of fatty fish, rich in omega-3 polyunsaturated fatty acids (3-PUFAs) reduces the severity and number of arrhythmias. Long term 3-PUFA-intake modulates the activity of several cardiac ion channels leading to cardiac action potential shortening. Circulating 3-PUFAs in the bloodstream and incorporated 3-PUFAs in the cardiac membrane have a different mechanism to shorten the action potential. It is, however, unknown whether circulating 3-PUFAs in the bloodstream enhance or diminish the effects of incorporated 3-PUFAs. In the present study, we address this issue. Rabbits were fed a diet rich in fish oil (3) or sunflower oil (9, as control) for 3 weeks. Ventricular myocytes were isolated by enzymatic dissociation and action potentials were measured using the perforated patch clamp technique in the absence and presence of acutely administered 3-PUFAs. Plasma of 3 fed rabbits contained more free eicosapentaenoic acid (EPA) and isolated myocytes of 3 fed rabbits contained higher amounts of both EPA and docosahexaenoic acid (DHA) in their sarcolemma compared to control. In the absence of acutely administered fatty acids, 3 myocytes had a shorter action potential with a more negative plateau than 9 myocytes. In the 9 myocytes, but not in the 3 myocytes, acute administration of a mixture of EPA+DHA shortened the action potential significantly. From these data we conclude that incorporated 3-PUFAs into the sarcolemma and acutely administered 3 fatty acids do not have a cumulative effect on action potential duration and morphology. As a consequence, patients with a high cardiac 3-PUFA status will probably not benefit from short term 3 supplementation as an antiarrhythmic therapy.